Third-line sunitinib treatment in a VHL-mutated metastatic intrahepatic cholangiocarcinoma: a case report and literature review. Issue 9 (1st September 2020) - Li, Xiaofen; Gao, Limin; Zhang, Li; Sun, Hongna; Gou, Hongfeng
ABSTRACT: Intrahepatic cholangiocarcinoma (iCCA) is a highly aggressive malignancy with a poor prognosis. There is no standard treatment beyond first-line chemotherapy and no molecular-targeted drug approved for advanced iCCA. We herein present a case of a 46-y-old Asian iCCA patient with multiple metastases in lung, bone, and liver. The patient progressed rapidly after first- and second-line chemotherapy. According to next-generation sequencing result of somatic Von Hippel–Lindau ( VHL ) gene mutation, the patient was administered third-line sunitinib and obtained a relatively longer survival of 9 months after taking sunitinib. Additionally, we briefly summarized the current targeted treatment of iCCA. To our knowledge, this is the first report of VHL mutation and sunitinib usage in metastatic iCCA patient. As a highly heterogeneous and aggressive malignancy, we strongly recommend making clinical decisions based on precision medicine concept in advanced iCCA.